The Polarization of Orientation on Cultural Land Utilization for Ecotourism Development Amongst the Local in Bali Aga of Mount Lesung Region - Putu Agus Haribawa; Ricky Avenzora; Harnios Arief (Institut Pertanian Bogor (IPB University), 2020)
The ownership transfer and conversion of cultural lands are a long-standing crucial issue in the dynamics of tourism development in Bali, so efforts to build a harmonious orientation among stakeholders in creating sustainable cultural land utilizations are important. For that matter, this research was conducted to study the phenomenon of polarization orientation on cultural land utilization of ecotourism development in Bali Aga. The assessment of cultural land sustainability was conducted using One Score One Indicator Scoring System analysis, with research aspects including ownership, economic, ecological, socio-cultural and spatial aspects. Besides, the polarization of stakeholder orientation was measured through perception, motivation, and preference, then, it was analyzed using Kruskal Wallis and Dunn Tests. The results of One Score One Indicator Scoring System analysis showed that the community has implemented various principles of sustainability in the utilization of cultural land in the Bali Aga region. The sustainable cultural land utilization in the Bali Aga region has not been fully achieved because the stakeholder orientation on various aspects and assessment criteria still experience polarization. Although the polarization orientation is still at the level of polarization scale, it can trigger future problems if the polarization is not well minimized by various stakeholder elements.